Switchable Filter For UHF Band - Sedlák, Milan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
The contribution deals with the design of a multi-channel switchable filter for ultra high frequency band. The device is primarily designed for the system of sensors which are used for detection of the electromagnetic pulses. They are emitted by the partial discharges in power transformers as a consequence of aging of the dielectric. The main task of the multi-channel switchable filter is to ensure better reliability of the entire system by filtering of undesirable signals with lower frequencies content which are usually products of the external and internal disturbance.
Keywords: Ultra high frequencies; multi-channel switchable filter; partial discharge; interferences